Uso De Escoria De La Central Termoeléctrica Termozipa Para Mezclas De Concreto - Morales Tapiero, Jhon Sebastián (Universidad Antonio Nariño, 2025)
The research was carried out with the purpose of examining the behavior of the compressive strength of a concrete mix design with fly ash aggregate, generated in the Termozipa thermoelectric plant, with the purpose of creating a use in the sector of the construction of the waste produced, thus promoting economic sustainability. The experimental findings were achieved through laboratory tests established by the Colombian Technical Standards, determining that Termozipa fly ash is not viable to be used as an additive in concrete mixtures due to the notable reduction in resistance and its addiction. does not generate a considerable benefit compared to a conventional mix design